Interactive Digital Learning in a University Lecture Room - Sihvonen, Mika (Proceedings of the International Conference on Networked Learning, 2018)
This article examines modern methods for higher education digital pedagogy in a lecture room. Over the last ten years, technology has changed lecturing in many different ways. Most of the students entering the university are in their twenties and therefore are seen as experienced in, and capable of, utilizing modern tools for communication. The research data for this paper was drawn up from two university courses which utilized several digital tools alongside other traditional lecture room teaching methods. The essential purpose of this paper is to increase understanding of students’ habits and needs concerning digital media use during the lectures. Course teachers have numerous ways to engage the students in the lecture situation, and during the course. Although educational technology is available, with low costs for mobile devices and Internet browser environments, the traditional face-to-face discussions are still relevant. Learning goals should define the expectations which are placed on the different tools. Course teachers should also be reminded that tool registration, as well as trial tests, are time-consuming. In addition, their operation in a teaching situation might require robust guidance or teaching assistants. This paper especially examines five tools for lecture/course activation - image wall, web-based voting, small group discussions, project blogs and online video. According to the results, students can be extremely active users of digital tools and media in some fields and yet uninterested in other uses of digital resources. 28 out of 30 respondents had a mobile device with them, but less than half felt the device was suitable and natural for lecture activities. Even if the students have a mobile device while attending the lecture room, a majority of them find teacher-guided digital activities laborious and extraneous. 26 respondents would participate in the lectures whether or not the recordings are available. All university students may need technical support, for discussions, and with enthusiasm for the use of educational technology, regardless of their age or whether they own a mobile device. Learning cannot be outsourced to discussion forums or blog platforms, but they can serve as excellent resources for learning community communication and as support for the learning process.